Prospects of development of the mediation model in Ukraine on the example of some Post-Soviet Union republics (Belarus, Moldova, Georgia) - Dolianovska, Inna; Lotariev, Andrii; Доляновська, Інна Миколаївна; Лотарєв, Андрій Григорович; Доляновська, Інна (Університет «КРОК», 2021)
Alternative dispute resolution (ADR) is a group of processes through which disputes and conflicts are resolved without recourse to the formal judicial system. These include: negotiation, arbitration and mediation. Mediation is an alternative method of resolving disputes with the involvement of a neutral third party - a mediator. Mediation has been used successfully in many European countries and has proven to be an effective method of settling disputes. However, each country has taken its own authentic path to the introduction and promotion of mediation. Despite the fact that mediation has existed in Ukraine for more than twenty years, we remain at the beginning of the path of development and implementation of this alternative method of dispute reso- lution. Mediation has not yet become a common method of resolving conflicts in our society, moreover, some participants in conflicts are unaware of the existence of such a method or have a misconception about where and when mediation can be used. Like many countries where mediation is already a mandatory pre-trial procedure, Ukraine has faced a number of challenges in implementing this alternative method of conflict resolution. Research on these issues and obstacles to the implementation of mediation in Ukraine will facilitate its rapid implementation. A comprehensive and in-depth study of all the positive and negative factors that have ac- companied the introduction of alternative dispute resolution methods in other countries will allow to avoid mistakes, strengthen the positive aspects and influence the negative factors. Therefore, the article will consider models of mediation development in some post-Soviet countries to find the most optimal way of development in this direction for Ukraine.
Keywords: mediation model; mediation process; development of mediation in Ukraine